1992
DOI: 10.1111/j.1464-5491.1992.tb01906.x
|View full text |Cite
|
Sign up to set email alerts
|

A Community Survey of Diabetes in the Elderly

Abstract: All 98 elderly patients who were known to have diabetes on the lists of two inner-city general practices were interviewed and examined in their own homes. They were characterized in terms of their prevalence of vascular complications, metabolic control, perceived health (measured by the Nottingham Health Profile), frequency of hospital and general practice contacts and use of domiciliary 'support services' and compared to 98 control subjects with an identical age/gender distribution. Mean haemoglobin A1 in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…It was similar to the difference between men and women (6% of the scale maximum), and cannot definitely be ascribed to insulin per se because insulintreated patients were younger and had been diabetic longer. In previous studies we (5) and others (13,14) have found that patients with complications had worse perceived health. Insulin-treated patients in the present study may well have had more complications, confounding the apparent relationship between insulin treatment and well-being.…”
Section: Correlates Of Well-being and Treatment Satisfactionmentioning
confidence: 68%
See 3 more Smart Citations
“…It was similar to the difference between men and women (6% of the scale maximum), and cannot definitely be ascribed to insulin per se because insulintreated patients were younger and had been diabetic longer. In previous studies we (5) and others (13,14) have found that patients with complications had worse perceived health. Insulin-treated patients in the present study may well have had more complications, confounding the apparent relationship between insulin treatment and well-being.…”
Section: Correlates Of Well-being and Treatment Satisfactionmentioning
confidence: 68%
“…Mean age was 71 ± 7 years for the responders, 72 ± 7 years for the patients who did not reply (nonresponders), and 72 ± 7 years for the 793 patients who were not selected. Median duration of diabetes was 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years in all groups. Women constituted 49% of responders, 50% of nonresponders, and 49% of nonselected patients.…”
Section: Response Rate and Demographic Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 23 However, a lack of agreement on the definition of quality of life means that a wide range of quality of life profiles and indices are used to assess health related distress. Such variety has complicated the validation and comparison of findings.…”
Section: Discussionmentioning
confidence: 99%